Apical vertebrae vs lung function in adolescent idiopathic scoliosis (AIS) - Johari, Joehaimey; Sharifudin, Mohd Ariff; Ab Rahman, Azriani; Omar, Ahmad Sabri; Abdullah, Ahmad Tajudin; Nor, Sobri; Lam, Andrew; Yusof, Mohd Imran (2014)
A retrospective record review was conducted among patients with adolescent idiopathic scoliosis (AIS) aged 13 to 24 years, admitted to our institution for surgical intervention from 2000 to 2013. A total of 38 patients were studied to determine apical veretebrae location and lung function. The curvature of spinal deformity was measured by Cobb method on anterior-posterior radiographs. The forced vital capacity (FVC) and forced expiratory volume in 1 second (FEV 1) were used to evaluate their pre-operative pulmonary function. Simple linear regression was performed to analyse the relationship between Cobb angle and pre-operative pulmonary function. Kruskal-Wallis and Mann Whitney tests were used to compare the lung function according to the severity of the deformity and different levels of affected spinal vertebra. A total of 38 patients were studied that involved thoracic and thoracolumbar scoliosis. The median FVC was significantly higher in those with affected apical vertebrae located at L1, L2 and L3 levels (median =92; IQR= 30) than those with apical vertebra at T6, T7 and T8 (median =68.5; IQR= 36) (p=0.008). The median FVC was also significantly higher in those with affected apical vertebra located at L1, L2 and L3 (median =92; IQR =30) than those with affected T9-T12 (median =74; IQR= 19 (p=0.003). In conclusion, impairment of lung function was seen in more severe spinal deformity and more proximally located curve.